2022
DOI: 10.1001/jamanetworkopen.2021.45697
|View full text |Cite
|
Sign up to set email alerts
|

Association of Major Depressive Symptoms With Endorsement of COVID-19 Vaccine Misinformation Among US Adults

Abstract: IMPORTANCEMisinformation about COVID-19 vaccination may contribute substantially to vaccine hesitancy and resistance. OBJECTIVE To determine if depressive symptoms are associated with greater likelihood of believing vaccine-related misinformation. DESIGN, SETTING, AND PARTICIPANTS This survey study analyzed responses from 2 waves of a 50-state nonprobability internet survey conducted between May and July 2021, in which depressive symptoms were measured using the Patient Health Questionnaire 9-item (PHQ-9). Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…This could give the impression that further measures against the pandemic are not necessary, since in parallel to this, many Latin American countries lifted some restriction measures [ 32 ]. In the case of people with depression, it is described that they are more likely to endorse false statements about COVID-19 and have half the likely to be vaccinated compared with those without depression, being proposed that a lack of positive interpretation bias or optimistic beliefs could conditionate those results mentioned above [ 33 ]. Additionally, there has been physical and mental exhaustion due to the restrictions related to the pandemic called “pandemic fatigue”, which causes people to decrease adherence to measures to prevent infection compared to the start of the pandemic [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could give the impression that further measures against the pandemic are not necessary, since in parallel to this, many Latin American countries lifted some restriction measures [ 32 ]. In the case of people with depression, it is described that they are more likely to endorse false statements about COVID-19 and have half the likely to be vaccinated compared with those without depression, being proposed that a lack of positive interpretation bias or optimistic beliefs could conditionate those results mentioned above [ 33 ]. Additionally, there has been physical and mental exhaustion due to the restrictions related to the pandemic called “pandemic fatigue”, which causes people to decrease adherence to measures to prevent infection compared to the start of the pandemic [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common findings in the studies considered for this review, is that patients with mental illnesses typically had lower vaccination rates or more vaccination hesitancy ( Eyllon et al, 2022 ; Huang et al, 2021 ; Jefsen et al, 2021 ; Bai et al, 2021 ; Perlis et al, 2022 ; Hao et al, 2021 ) confirming a numerous studies suggesting this (Wang et al, 2021). Specifically, individuals with severe mental illness, including schizophrenia, were least likely to accept vaccination ( Huang et al, 2021 ; Bai et al, 2021 ; Tzur Bitan et al, 2021 ; Raffard et al, 2022).…”
Section: Discussionmentioning
confidence: 61%
“… Perlis et al (2022) found that presence of depression was significantly associated with increased likelihood of endorsing misinformation, which was associated with decreased likelihood of vaccination willingness. Further, they found that respondents who endorsed at least one misinformation item were significantly less likely to be vaccinated, but also significantly less likely to have a vaccinated family member ( Perlis et al, 2022 ). These findings persisted even after adjustment for sociodemographic features, and self-reported ideology or political party affiliation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Consequently, individuals with these issues are less likely to engage in proactive, self-care behaviors. Individuals who endorse symptoms of depression appear susceptible to misinformation about COVID-19 vaccines [ 19 ], and a recent review of the relevant research to date found fear and anxiety were associated with COVID-19 hesitancy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%